Vicissitudes - Maidanik, Victoria (Université McGill, 1997)
Vicissitudes is a composition for orchestra with a duration of approximately 13$ sp prime$ 30$ sp{ prime prime}$. The main idea of the piece, the subdivision of the orchestra into small soloistic groups along with larger ensembles, was inspired by the principles of one of the Baroque forms, namely the Concerto Grosso.

A Bosnian Sephardic Woman in Kahnewake, Quebec - Cohen, Judith R. (Canadian Woman Studies/Les cahiers de la femme, 1996)

Commentaires sur Ambient V, Secret de polichinelle et Danga - Sokolovic, Ana (Université de Montréal, 1996)

Women's Roles in Judeo-Spanish Song Traditions - Cohen, Judith R.; Sacks, Maurie (Active Voices: Women in Jewish Culture, 1995)

When Shirley Met Florence - Bezalel, Ronit (Office national du film du Canada, 1994)
Portrait intime de deux femmes juives au milieu de la soixantaine, l'une homosexuelle et l'autre hétérosexuelle, dont l'amour l'une pour l'autre et la musique qu'elles créent ensemble transcendent les différences. L'attachement de Florence pour Shirley défie toute catégorisation.

Expressive Modes in the Judeo-Spanish Wedding Song - Anahory-Librowicz, Oro (New Horizons in Sephardic Studies, 1993)

The Music of the Songs: Musical Transcriptions and Commentary of the Songs Discussed by Oro Anahory-Librowicz "Expressive Modes in the Judeo-Spanish Wedding Song" - Cohen, Judith R. (New Horizons in Sephardic Studies, 1993)

Women and Judeo-Spanish Music - Cohen, Judith R. (Bridge, 1993)

Canada 125. Cantate profane pour chœur et orchestre, analyse musicologique - Badian, Maya (Lucian Badian Editions, 1992)

The Odyssey of Dahlia Obadia: Morocco, Israel, Canada - Sawa, Suzanne Myers (Canadian Folk Music Journal, 1991)
Dahlia Obadia interprète les danses de la tradition du moyen orient. Pendant sa carrières, elle a rémarque qu’il existe des grandes différences entre les interprétations de cette tradition vue de l’intérier et de l’extérieur. L’auteur décrit la vie de Dahlia et explore les problèmes qu’elle a affrontes pendant sa quête de sa propre identité culturelle.